2003
DOI: 10.1097/00003226-200308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Limbal Stem Cell Deficiency by Corneal Impression Cytology

Abstract: Immunocytochemistry for seeking out CK19- and CK3-positive cells on corneal IC is a simple and practical method to investigate LSCD. We believe that this technique could have an important role in evaluating patients undergoing therapeutic penetrating keratoplasty to select those who would benefit from limbal stem cell transplantation. Since sampling has been shown to be a critical point, we believe that any improvement in this area will also help to improve the methodology and will contribute to its wider util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
79
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 22 publications
4
79
1
3
Order By: Relevance
“…3,4 Nevertheless, corneal impression cytology is not a routine clinical procedure in contact lens practice. Donissi and colleagues, 4 concluded that impression cytology could have an important role in evaluating patients undergoing therapeutic penetrating keratoplasty to select those who would benefit from limbal stem cell transplantation. Impression cytology is essential to confirm if these patients have LSCD induced by contact lens wear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 Nevertheless, corneal impression cytology is not a routine clinical procedure in contact lens practice. Donissi and colleagues, 4 concluded that impression cytology could have an important role in evaluating patients undergoing therapeutic penetrating keratoplasty to select those who would benefit from limbal stem cell transplantation. Impression cytology is essential to confirm if these patients have LSCD induced by contact lens wear.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Patients with LSCD can present with a range of symptoms, including irritation, photophobia and decreased visual acuity. 3,4 The diagnosis relies on laboratory tests such as impression cytology to detect the presence of goblet cells or the expression of certain types of keratin in corneal epithelium. 3,4 Corneal diseases that manifest LSCD can be subdivided into two major categories.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Las alteraciones a nivel del limbo producen importantes trastornos a nivel del la superficie del epitelio corneal que pueden ser detectados mediante la citología de impresión (18). En este trabajo planteamos un estudio trasversal para determinar las características citológicas del epitelio corneal en diferentes entidades etiológicas que tienen en común la presencia de un cuadro de deficiencia limbal.…”
Section: Discussionunclassified